2003
DOI: 10.1124/mol.63.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Structure on Substrate Binding to the Human Organic Cation Transporter, hOCT1

Abstract: Organic cation transporters play a critical role in the elimination of therapeutic compounds in the liver and the kidney. We used computational quantitative structure activity approaches to predict molecular features that influence interaction with the human ortholog of the organic cation transporter (hOCT1). [ 3 H]tetraethylammonium uptake in HeLa cells stably expressing hOCT1 was inhibited to varying extents by a diverse set of 30 molecules. A subset of 22 of these was used to produce, using Catalyst, a phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 19 publications
12
103
0
Order By: Relevance
“…It is of interest to note that the model developed in this latter study is similar to the previously reported pharmacophore which contained three hydrophobic sites and a positive ionizable site where the calculated distances between the positive ion site and the three hydrophobic sites were 4.2, 5.1 and 5.3 Å (Bednarczyk et al 2003). If the three hydrophobic sites postulated in the earlier work are considered to be a single hydrophobic area, then the major differences between the two models are the added hydrogen bonding areas.…”
Section: Pharmacophore Modelling Of the Interactions Of Small Moleculsupporting
confidence: 74%
See 4 more Smart Citations
“…It is of interest to note that the model developed in this latter study is similar to the previously reported pharmacophore which contained three hydrophobic sites and a positive ionizable site where the calculated distances between the positive ion site and the three hydrophobic sites were 4.2, 5.1 and 5.3 Å (Bednarczyk et al 2003). If the three hydrophobic sites postulated in the earlier work are considered to be a single hydrophobic area, then the major differences between the two models are the added hydrogen bonding areas.…”
Section: Pharmacophore Modelling Of the Interactions Of Small Moleculsupporting
confidence: 74%
“…The identification and characterization of interactions with the hOCT1 has been primarily accomplished using cellular uptake and trans -stimulation studies (Zhang et al 1999; Bednarczyk et al 2003), which are complicated and variable. The development of a CMAC(hOCT1) column has recently been reported as an alternative approach to the determination of hOCT1 binding interactions (Moaddel et al 2005b).…”
Section: Determination Of Stereoselective Ligand Interactions With Drmentioning
confidence: 99%
See 3 more Smart Citations